Futures of Civil Aviation Operations explored from the perspective of Finnair - Ivanov, Krasimir (My University, 2023)
Civil aviation is one of the busiest transport sectors which to this day has no competitors when it comes to speed and efficiency of transporting passengers and goods all around the world. Because of this the industry is constantly developing and trying to meet the huge demand for its services. The world economy directly depends on its main carrier, without which world trade would not be carried out in such large volumes and at such a fast pace. However, the function of civil aviation is totally dependable on various factors that directly or indirectly affect it. If we were only to look at the biggest pieces of the puzzle, such as the economy, politics and environmental changes, it could be easier to predict the future direction of civil aviation. However, we are left flustered when critical events, the so-called wild cards such as the COVID- 19 pandemic, occur. Such events have already proved to us that they can in the worst case scenario completely suspend civil aviation operations and lead to the stagnation of global economy. The purpose of this study is to go beyond the obvious and to identify some of the most important underlying factors which are likely to affect the future of aviation in the next twenty years. The aviation industry goes tightly together with the forefront of technology and is in the middle of search for innovations that can help achieve a more sustainable world where civil aviation still exists. Climate change is forcing the aviation industry, among many other fields, to look for solutions to drastically cut their carbon emissions while subsequently more and more consumers are choosing to minimize their carbon footprint and avoid air travel. Moreover, climate change is not the only struggle aviation has to face in the future. The war in Ukraine has showed us how much of an inconvenience wars and military operations can be for civil aviation with plane routes being re-directed to avoid war-zones adding thousands of miles into their journey. Likewise the safety of civil aviation is always at risk when military actions including missiles are carried out, and even outside of war the industry still has not reached a 100% flight safety despite the extensive efforts of building safer and more reliable aircrafts. In addition, the industry which once was the crown jewel of human innovation is having to face the harsh reality that modern artificial intelligence might one day take over some of the key elements of aviation including piloting the planes. These among other factors will most likely affect civil aviation in the next 20 years. The images of the future presented in this study and identified as critical are based directly on these scenarios and are backed up by information obtained from suitable sources on this topic.
Keywords: civil aviation, images of the future, wild card, key factors